POTENSI ANTIBAKTERIA EKSTRAK DAN FRAKSI LIBO (Piper miniatum BL) - Priyono, Sumarnie -H (BERITA BIOLOGI, 2008)
Libo (Piper miniatum Bl.) is traditionally used in Papua as spices and tonic. Besides as food flavor, it is commonly used as food natural preservative that is related to its antibacterial activity. But so far, there is no scientific report about antibacterial activity from the plant extract.The antibacterial activity test result in this study, showed that the four extracts (n-hexane, chloroform, ethyl acetate and methanol) of libo were active against Streptococcus mutants (BCC1863) and Staphylococcus aureus (ATCC 25923). The extracts were active only on high consentration againts Pseudomonas aeruginosa (ATCC 27853) and Escherichia coli (ATCC 25922), meanwhile on Salmonella enteriditis (BCC 2754), Staptylococcus epidermidis strain Cowan (BCC 1820) and Bacillus subtilis (ATCC 10400) gave different antibacterial effect. The n-hexane extract has the highest antibacterial activity againts S. mutans (BCC 1863). Fractionation result of n-hexane extract, F3 and F4 at concentration 124.4|ig showed antibacterial effect against Listeria monocytogenes (M 19117) equivalent to erythromycin 10 \g as standart antibiotic. While Fl and F2 at concentration 124.4|ig had antibacterial activity against E. coli (ATCC 25922) equivalent to erythromycin 10 ug.